Foreword—Breaking barriers in chemical biology: the innovative tour de force of the ChemBio GDR - Lopez, Marie; Mileo, Elisabetta; Defrancq, Eric; Delmas, Agnès; Vauzeilles, Boris; Guianvarc’h, Dominique; Biot, Christophe (Comptes Rendus. Chimie)
Chemical Biology can be defined as the design and the development of molecular tools to decipher or modulate biological processes of interest so that they can be better understood, controlled or modified. It also consists in the observation and analysis of these molecular tools within, and in interaction with, their complex biological environment. Chemical Biology can then lead to highly valuable basic knowledge and be applied in diverse fields such as health and environment. Therefore, Chemical Biology has strong interactions with the design of therapeutic strategies, diagnosis, agrochemicals or Ecology.